LncRNA UCA1 stimulates proliferation, invasion and EMT of cutanous squamous cell carcinoma A431 cells through miR-143/HK2 axis - Yonghong ZHANG; Cuntao LI; Yuhong ZHANG; Li YAO (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2021)
Objective: To investigate the expression levels of long noncoding RNA UCA1 in A431 cells and its effects on proliferation, invasion and epithelial-mesenchymal transition of A431 cells. Methods: The expression levels of lncRNA UCA1 in skin squamous cell carcinoma, paracancerous tissues, A431 cells and HaCaT cells were assessed by Quantitative Real-time PCR.Following down-regulation of lncRNA UCA1 with siRNA, proliferation, invasion and EMT of A431 cells were measured by methyl thiazolyl tetrazolium, Transwell and Western blot, respectively. The relationship between lncRNA UCA1 and microRNA-143 was analyzed by miRanda and double luciferase reporter gene assay. RT-qPCR was used to determine the expression levels of miR-143 in A431 cells and HaCaT cells. To determine whether the effects of lncRNA UCA1 is via miR-143, proliferation, invasion and EMT of A431 cells were analyzed following simultaneous upregulation of lncRNA UCA1 and miR-143. The relationship between miR-143 and Hexokinase II was analyzed by TargetScan and double luciferase reporter gene assay. RT-qPCR was used to detect HK2 expression in A431 cells and HaCaT cells. Proliferation, invasion and EMT of A431 cells were analyzed following down-regulation of HK2 with siRNA. Results: In A431 cells, the expression levels of both lncRNA UCA1and HK2 were upregulated (P<0.01), while the expression levels of miR-143 were down-regulated (P<0.01). Down-regulation of lncRNA UCA1 significantly inhibited proliferation, invasion and EMT of A431 cells. lncRNA UCA1 negatively regulated miR-143 expression.Down-regulation of miR-143 stimulated proliferation, invasion and EMT of A431 cells. Upregulation of lncRNA UCA1 promoted proliferation, invasion and EMT of A431 cells through miR-143.Down-regulation of HK2 with siRNA inhibited A431 cell proliferation, invasion and EMT. lncRNA UCA1 upregulated HK2 expression through miR-143. Conclusions: Expression of lncRNA UCA1 is upregulated in cutaneous squamous cell carcinoma A431 cells. lncRNA UCA1 stimulates proliferation, invasion and EMT of A431 cells through miR-143/HK2 axis.